Don't get in a flap!: A case report of progression through the spectrum of an acute aortic syndrome. (December 2014) - Choong, Andrew MTL; Das, Saroj; Mulrenan, Nicholas; Hamady, Mohamad; Bose, Protip
Purpose: To present a single case that clearly demonstrates the progression through the whole spectrum of an acute aortic syndrome, from a solitary penetrating aortic ulcer (PAU) through to multiple PAUs with intra-mural haematoma (IMH) progression. The index images show that despite the clinical presentation of an acute type B aortic dissection, a classical dissection flap is never demonstrated in this patient and thus highlights the need for early input from vascular surgery for all potential acute aortic syndromes. Case report: We present the case of a 71-year-old lady who attended the emergency department with hypertension and inter-scapular chest pain. Upon investigation with computed tomography aortography (CTA), she was found to have a solitary PAU only with minimal IMH. She did not demonstrate any classical radiological signs of acute type B aortic dissection. She was admitted under a medical team and her chest pain abated with no treatment. The treating medical team adjusted her anti-hypertensive medication and discharged her home with an urgent vascular surgical outpatient appointment for further follow-up and surveillance. We acknowledge that a preferred approach would have been, at least admission and close blood pressure monitoring, with a repeat CTA the next day. Two days later, she represented with further chest pain and on repeat CTA was found to have multiple PAUs and progression of the small IMH. She was then admitted under vascular surgery and subsequently transferred to the parent tertiary referral vascular surgical unit. Despite aggressive anti-hypertensive management, she had persistent intractable chest pain and was treated with a single thoracic stent graft. Completion angiography demonstrated total resolution of the PAUs. Conclusion: This case along with index images demonstrates the whole spectrum of the acute aortic syndrome from a solitary PAU to multiple PAUs with IMH extension. Despite an eventual clinical picture of an acute type B aortic dissection, there was a notable absence of a classical dissection flap on any imaging. We recommend that all aortic pathologies should be at least discussed with and preferably managed by vascular surgeons. The absence of a classical dissection flap on imaging is not a contra-indication to emergent treatment with thoracic stent grafting and in select patients is actually the only therapy that will treat this pathology.